Respuesta :

Answer:

y = -45x + 13

Step-by-step explanation:

The equation is *** y = [tex]-5x^{2}[/tex]  - 20x +13 ***

First: you have to look at [tex]-5x^{2}[/tex]  which would equal -25x

Second: you have take the -25x and put into the equation... y = -25x - 20x +13

Third: You have subtract -25x - 20x which equals -45x

Lastly: Now you have y = -45x + 13 and since 13 does NOT have a variable like -45x does, you then know that you have finished the equation

The person above me is right G ood day to you!!